Three new recorded species of the genus Dalbergia (Fabaceae: Papilionoideae: Dalbergieae) from southwestern China - Dong, Jin-Long; Jiang, Kai-Wen; Biao, A.; Shu, Nan; Huang, Hui-Wen; Song, Zhu-Qiu; Pan, Bo; Tu, Tie-Yao; Li, Shi-Jin (Phytotaxa, 2025)
This study documents three Dalbergia tree species—D. lanceolaria L. f., D. nigrescens Kurz, and D. oliveri Gamble ex Prain—as new records for the flora of China. All three species belong to the section Dalbergia and were collected from Yunnan Province in southwestern China. This article provides detailed descriptions, phenological data, distribution information, habitat details, and taxonomic remarks for each species. A key to the Chinese species within the section Dalbergia is also included.